Accumulation of phosphorylated tyrosine hydroxylase into insoluble protein aggregates by inhibition of an ubiquitin–proteasome system in PC12D cells - Kawahata, Ichiro; Tokuoka, Hirofumi; Parvez, Hasan; Ichinose, Hiroshi (Journal of Neural Transmission, 2009)
Tyrosine hydroxylase (TH) is a rate-limiting enzyme for the biosynthesis of catecholamines including dopamine. The relationship between proteasomal dysfunction and the etiology of Parkinson’s disease has been suggested, but it is unknown if TH protein is affected by proteasomal dysfunctions. Here, we examined the effect of inhibition of ubiquitin–proteasomal pathway on biochemical characteristics of TH protein in the neuronal cells. Inhibition of 20S or 26S proteasome by proteasome inhibitor I, or MG-132 in NGF-differentiated PC12D cells induced dot-like immunoreactivities with the anti- 40 Ser-phosphorylated TH (p40-TH) antibody. These dots were tightly co-localized with ubiquitin and positive to Thioflavine-S staining. These dot-like immunoreactivities were not obvious when immunostaining was performed against total-TH or choline acetyltransferase. Western blotting analysis showed time-dependent increase of p40-TH in the Triton-insoluble fractions. We also examined the effect of okadaic acid, an inhibitor of protein phosphatase 2A, which is a phosphatase acting on p40-TH. Okadaic acid increased the amount of insoluble p40-TH. These data suggest that p40-TH is prone to be insolubilized and aggregated by dysfunction of an ubiquitin–proteasome system in PC12D cells.